Pengaruh Belajar Aqidah Akhlak Terhadap Pembentukan Karakter Siswa Madrasah Aliyah Alkhairaat Falabisahaya - Maani Pora (IAIN Ternate, 2022)
This study aims to determine the effect of Aqidah Ahlak learning outcomes on theformation of student character. This study uses a qualitative approach, because the data presented are in the form of numbers. implementation, Aqidah Akhlak learning at Madrasah Aliyah Alkhairaat Falabisahaya This article uses a qualitative research type with a case study approach. The researcher's data collection technique was by conducting participant observation, documentation, and interviews. The data sources of this research were 38 madrasah students, . Based on the results of the study, it was concluded that there was an influence on the learning outcomes of aqidah ahlak and could have an influence on the character of students.